Pengembangan Alat Praktikum Kesetimbangan Kimia Untuk Siswa SMA di Pontianak - leni susanti; Raudhatul Fadhilah; Tuti Kurniati (Universitas Pendidikan Mandalika Mataram, 2022)
The practicum method in chemistry subjects, especially in chemical equilibrium material, is still rare and has never been carried out in schools due to the unavailability of adequate practicum tools. Therefore, a practical tool is needed to make it more straightforward for understudies to comprehend the idea of equilibrium shift. This study aims to develop a chemical equilibrium practicum tool on the sub-material of equilibrium shift that is legitimate, commonsense and powerful. This sort of exploration is Innovative work (Research and development) model ADDIE (Investigation, Plan, Improvement, Execution, Assessment). The research subjec was 33 students from two private schools in Pontianak, with 15 and 18 students, respectively. The results showed that the chemical equilibrium practicum instrument created from the material and media viewpoints was pronounced substantial with a typical legitimacy worth of 0.87 and 0.9 with both extremely legitimate rules. The consequences of the reasonableness test got extremely down to earth models with a worth of 98.23%. The part of viability by involving the N-Gain esteem in field preliminaries, the N-Gain esteem is 0.8 with extremely high measures. In this manner the synthetic balance practicum instrument created is doable to be utilized as a learning medium in the sub-material of equilibrium shift.